The Optimal Chinese Herbal Injections for Use With Radiotherapy to Treat Esophageal Cancer: A Systematic Review and Bayesian Network Meta-Analysis - Zhang, Dan; Ni, Mengwei; Wu, Jiarui; Liu, Shuyu; Meng, Ziqi; Tian, Jinhui; Zhang, Xiaomeng; Zhang, Bing (Frontiers in Pharmacology, 2019)
Abstract Background: Esophageal cancer is one of the most common human cancers, and its incidence is significantly endemic in China. The combination of Chinese herbal injections (CHIs) with radiotherapy should be informed by the best available evidence. To update and expand the previous work to compare and rank CHIs combined with radiotherapy against esophageal cancer. Methods: We searched several electronic databases to identify randomized controlled trials (RCTs) regarding CHIs against esophageal cancer from their inception to Mar 15, 2017. In network meta-analysis (NMA), and the bias of included trails was assessed in accordance to the Cochrane Handbook for Systematic Reviews of Interventions. Outcomes such as the clinical effectiveness rate, performance status, adverse reactions (ADRs) and survival rate were evaluated. We performed a random-effects NMA to obtain estimates for efficacy and safety outcomes and presented these estimates as odds ratios (ORs) and corresponding 95% confidence intervals (CIs) via Stata 13.1 and WinBUGS 1.4 software. Furthermore, the surface under cumulative ranking curve (SUCRA) was performed to rank efficacy and safety of different CHIs for outcomes. Results: We identified 685 citations and of these included 55 eligible trials comprising 12 CHIs and 4114 participants. The results of cluster analysis indicated that the therapy of Compound kushen injection might be the optimal treatment for patients with esophageal cancer in improving clinical effectiveness rate and performance status than other CHIs. Besides, Huachansu and Kangai injection exhibited the superior response for improving 1-year and 2-year survival rate. Moreover, Lentinan injection may be considered as a favorable choice for reliving ADRs, and Compound kushen injection could provide treatment benefits for reducing both gastrointestinal reaction and radiation esophagitis. Conclusions: The current clinical evidence indicated that Compound kushen injection combined with radiotherapy had the potential to be the most preferable and beneficial option for patients with esophageal cancer on balance of efficacy and safety. However, the results for our study should be interpreted with caution that limited by the sample size and methodological quality of included trails.